Assessment of periodontal diseases in epidemiological investigations: a critical review - Abdul-Kadir, R. (1989)
Like dental caries, epidemiological assessment of periodontal disease is important for purposes of recognizing the extent of the disease in the population as well as a basis for planning and evaluating preventive and treatment programmes. while present day measurement methods for dental caries are excellent such is not true for periodontal diseases. This paper reviews the development and usefulness of different indices for the assessment of periodontal disease and treatment needs in epidemiological investigations.